Asparagine promotes cancer cell proliferation through use as an amino acid exchange factor - Abigail S. Krall (Nature Portfolio, 2016)
Cancer cells have been shown to be dependent upon glutamine for growth. Here, the authors show that intracellular asparagine, a glutamine-derived metabolite, is critical to cancer cell growth and can compensate glutamine deficiency by acting as an amino acid exchange factor.